PERKEMBANGAN ISLAM DI TENGAH FENOMENA ISLAMOFOBIA DI JERMAN - Muhammad Wildan (TEMALI : Jurnal Pembangunan Sosial, 2019)
Although Islam in Europe is not a new phenomenon, Muslims in Germany are still quite remarkable to study. The dynamic of Muslims both internally and externally is the most interesting thing. Internally, Muslims in Germany who are coming from many different ethnics and races in Asia and Africa is a such a big challenge for Muslims to unite and integrate. Externally, Islam which is historically not a “homegrown” religion in Europe is facing such a big challenge to adjust to such a “new” circumstances. Judeo-Christian has long been the cultural tradition of Germans and Europeans in general. The influx of a number of Muslims from some conflict areas in the Middle East and Africa recently adds another notable phenomenon. This article is trying to portray the development of Islam and Muslims in Germany and the way how they mingle with German counterparts along with the growing of islamophobia in the country. Eventually, this article will also observe some resistance of Muslims in the form of radicalism in the country and their efforts to integrate into Western society.